Membangun Pariwisata Kelas Dunia: Peran Strategis Kebumen Geopark Youth Forum (KGYF) dalam Mewujudkan Geopark Kebumen sebagai UNESCO Global Geopark - Qibtiyya, Maria (Gadjah Mada Journal of Tourism Studies, 2025)
Kebumen Geopark, recognized at the national level and aspiring to attain UNESCO Global Geopark (UGGp) status, possesses significant geological heritage and tourism potential. Its sustainable development requires the active involvement of multiple stakeholders, with youth playing a key role. This study analyzes the roles of the Kebumen Geopark Youth Forum (KGYF) in advancing the geopark’s progress toward UGGp status, where youth engagement is a crucial evaluation criterion. This study applies the role theory proposed by Ife and Tesoriero (2006), which categorizes roles into Facilitative, Educational, Representative, and Technical. This research collects data through interviews, field observations, and literature reviews. The findings demonstrate that KGYF effectively undertakes all four roles by supporting tourism communities, articulating public aspirations, sharing knowledge, and managing organizational functions. KGYF’s external contributions are evident in initiatives such as the Conservation Fair, the Geopark Goes to School program, geo-product development assistance, digital marketing support, and tourism promotion through various media platforms. The continuation and enhancement of these initiatives by current and future members are essential for sustaining the development of Kebumen Geopark and achieving its long-term objectives.